2017
DOI: 10.1002/iub.1604
|View full text |Cite
|
Sign up to set email alerts
|

Membrane remodeling and organization: Elements common to prokaryotes and eukaryotes

Abstract: Membrane remodeling processes in eukaryotes, such as those involved in endocytosis and intracellular trafficking, are mediated by a large number of structural, accessory and regulatory proteins. These processes occur in all cell types, enabling the exchange of signals and/or nutrients with the external medium and with neighboring cells; likewise, they are required for the intracellular trafficking of various cargo molecules between organelles, as well as the recycling of these structures. Recent studies have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…These properties might be an alternative method for parasite survival, remaining enclosed within cysts for a long period of time or, as proposed, for the entire life of the infected host [28,29]. These data point to the endocytosis, described for mammalian cells [30,31] as well as the endocytic pathway of other pathogenic protozoa [32], as a mechanism of tissue cysts during intracellular development for nutrient acquisition from the host cell.…”
Section: Discussionmentioning
confidence: 74%
“…These properties might be an alternative method for parasite survival, remaining enclosed within cysts for a long period of time or, as proposed, for the entire life of the infected host [28,29]. These data point to the endocytosis, described for mammalian cells [30,31] as well as the endocytic pathway of other pathogenic protozoa [32], as a mechanism of tissue cysts during intracellular development for nutrient acquisition from the host cell.…”
Section: Discussionmentioning
confidence: 74%
“…This research question is fundamentally motivated by the diverse range of physiological processes mediated by mitogenic and metabolic signals in mammalian cells, including cellular growth, proliferation, migration, and differentiation. These processes, to some degree, require both local and global plasma membrane remodeling events of which precise mechanisms however, remain relatively unexplored [59][60][61] . As a major regulator of the mammalian surfaceome, CME may therefore be implicated in facilitating plasma membrane remodeling required for cellular processes.…”
Section: -A Conceptual Map For the Reader: Topics To Be Discussedmentioning
confidence: 99%
“…Membrane organization, as well as lipid and protein constituents, complex membrane remodeling processes were thought to be an exclusive features of eukaryotic cells. Recently, it has been demonstrated that prokaryotic cells also undergo multiple membrane remodeling processes which are similarly controlled by specific proteins, analogous to the ones found in eukaryotic cells (Vega-Cabrera and Pardo-López 2017). Regardless of the different protein complexes involved for each organism, from a biophysical perspective, four basic molecular mechanisms have been described to remodel biological membrane, modifying their curvature (Figure 1) (Zimmerberg and Kozlov 2005) Those biophysical mechanisms are ubiquitous and involved in multiple physiological processes.…”
Section: Introductionmentioning
confidence: 97%